ESTIMATION EFFICIENCY OF REWOUND INDUCTION MOTORS IN SITU USING A NUMERICAL MODEL - Kaddari, Mohamed; Mouden, Mahmoud El; Hajjaji, Abdelowahed; Abdellah, Semlali (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents an effective technique for determining the impact of rewinding practices on the motor efficiency and characterizing the efficiency reduction when electrical motors are rewound several times. This technique focuses on a new approach and a statistical study to find a numerical model for the estimation efficiency of rewound induction motors in the field. The experimental results from 101 induction motor tests are analysed. A numerical model is determined and compared with different methods: separate losses method, modified current method and simple current method. An error analysis is conducted to examine the level of uncertainty by testing three asynchronous motors at 110 kW, 160 kW and 300 kW. The results show that this approach can predict and estimate the efficiency reduction in rewound motors without expensive tests and can help the energy manager make effective cost decisions in replacing the rewound motors with more efficient ones by using an assessment of overconsumption and maintenance costs. Another advantage of this model is that it can be used to improve the software tools and can also be a very strong indicator to audit the repair quality.